2019
DOI: 10.3390/ijerph17010181
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climate Change and the Snail-Schistosome Cycle in Transmission and Bio-Control of Schistosomiasis in Sub-Saharan Africa

Abstract: In the next century, global warming, due to changes in climatic factors, is expected to have an enormous influence on the interactions between pathogens and their hosts. Over the years, the rate at which vector-borne diseases and their transmission dynamics modify and develop has been shown to be highly dependent to a certain extent on changes in temperature and geographical distribution. Schistosomiasis has been recognized as a tropical and neglected vector-borne disease whose rate of infection has been predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 130 publications
0
51
0
Order By: Relevance
“…Kazibwe et al [ 42 ] and Chimbari et al [ 10 ] also noted the role played by these factors in the distribution of these snail species. Previous models have demonstrated that pH values and other physicochemical properties affect spatial distribution and snail densities [ 5 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kazibwe et al [ 42 ] and Chimbari et al [ 10 ] also noted the role played by these factors in the distribution of these snail species. Previous models have demonstrated that pH values and other physicochemical properties affect spatial distribution and snail densities [ 5 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, additional factors should be evaluated to accurately assess the future trend of schistosomiasis transmission in areas with rising sea levels. Besides salinity, climate change will also influence temperature, pH, rainfall, flooding, and drought [35]. Snail fitness is likely impacted by temperature alterations and drought, and these alterations certainly impact snail mortality and parasite production [20,3843].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, massive treatment with praziquantel and improving sanitation appear the best way to control the disease. However, new foci are appearing, and other are re-emerging probably due to global warming [ 38 , 39 ] and mass human migration [ 40 ], but also to the emergence of drug-tolerant schistosomes [ 41 , 42 ]. In this context, snail control appears to be a crucial strategy to ensure a sustainable control and elimination of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%